Risk assessment of antibody-mediated damage based on the detection of HLA and non-HLA antibodies toward extracellular antigens before kidney transplantation - Solà-Porta, Eulàlia; Redondo-Pachón, Dolores; Eguía-Núñez, Jorge; Buxeda, Anna; Caro, José Luís; Gimeno, Javier; Campuzano, Luís; Burballa, Carla; Chamoun, Betty; Sanz-Ureña, Sara; Federico-Vega, Judith; Alari-Pahissa, Elisenda; et al. (Frontiers in Immunology, 2025)
IntroductionDonor-specific human leukocyte antigens antibodies (HLA-DSA) contribute toantibody-mediated rejection (ABMR) after kidney transplantation (KT). Non-HLA antibodies may play a role in ABMR in the presence of HLA-DSA or the development of microvascular inflammation (MVI) in its absence. Considering both types of antibodies in potential recipients could enhance ABMR/MVI risk assessment.MethodsWe present a case-control study of 121 KT recipients, 46 with ABMR/ MVI diagnosis, and 75 control cases with available sera before and after KT, follow-up HLA antibody monitoring, and biopsies. We determined 60 serum non-HLA antibodies using a multiplex test with an established cutoff. We evaluated their association with ABMR/MVI using a sample median fluorescence intensity (MFI) ratio sum.ResultsFollowing commercial cutoffs, non-HLA antibodies were detected in 87% of the patients before KT. We found that a high non-HLA antibody MFI ratio sum before KT and at biopsy were associated with an increased risk of ABMR/MVI, independently of HLA sensitization or HLA-DSA (OR = 1.039, p = 0.014 and OR = 1.036, p = 0.024). Antibodies against extracellular non-HLA antigens were associated with ABMR/MVI before KT (OR = 1.053, p = 0.040), but at diagnosis, only antibodies against intracellular non-HLA antigens were associated (OR = 1.062, p = 0.018).ConclusionThese findings suggest that non-HLA antibody assessment offers valuable complementary information, regardless of HLA sensitization, though appropriate cut-offs should be explored.